The crystal growth kinetics of Bi2Sr2CaCu3Ox glass-ceramics - Koralay, H; Ceylan, M; Yavuz, H (Elsevier Science Sa, 2003)
A glass of nominal Bi2Sr2CaCu3Ox composition prepared by rapid-quenching of the melt, showed a glass transition temperature of 438 degreesC, crystallization temperature of 454 degreesC and melting temperature of 860 degreesC at 10 degreesC/min heating rate. The activation energy for crystallization of the glass has been estimated to be 348 kJ/mol from non-isothermal differential scanning calorimetry (DSC). A, Johnson-Mehl-Avrami analysis of DSC output gave an Avrami exponent n approximate to 2.5 indicating growth on pre-existing nuclei, as shown by microscopy observations. A melt-quenched samples annealed at 830 degreesC for 72 h was superconducting with the transition temperatures at zero resistance (T-c,T- zero) and the onset (T-c,T- onset) of 68 and 98 K, respectively, and transition width DeltaT(c) of 30 K. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: superconducting; activation energy; Avrami exponent